2006 Fortieth Asilomar Conference on Signals, Systems and Computers 2006
DOI: 10.1109/acssc.2006.355018
|View full text |Cite
|
Sign up to set email alerts
|

Real-time synthetic aperture imaging: opportunities and challenges

Abstract: Abstract-Synthetic aperture (SA) ultrasound imaging has not been introduced in commercial scanners mainly due to the computational cost associated with the hardware implementation of this imaging modality.SA imaging redefines the term beamformed line. Since the acquired information comes from all points in the region of interest it is possible to beamform the signals along a desired path, thus, improving the estimation of blood flow. The transmission of coded excitations makes it possible to achieve higher con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In SPA imaging with the described system, the bottleneck limiting the frame rate is the immense computational load required in synthetic beamforming. Our current efforts to improve the computational speed include utilizing a GPU and an FPGA for beamforming operations [25], [26]. New imaging methods for faster imaging, for example, CPA with multiline acquisition (CPA-MLA) [27]–[29] and flash imaging with multiple angles [30], are also being implemented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In SPA imaging with the described system, the bottleneck limiting the frame rate is the immense computational load required in synthetic beamforming. Our current efforts to improve the computational speed include utilizing a GPU and an FPGA for beamforming operations [25], [26]. New imaging methods for faster imaging, for example, CPA with multiline acquisition (CPA-MLA) [27]–[29] and flash imaging with multiple angles [30], are also being implemented.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that beamformers implemented with a GPU [25] or an FPGA [26] improve the ultrasound imaging system performance. New software performing computations on a GPU platform is under development, and an FPGA-based beamformer is also under consideration for our system.…”
Section: Real-time Imaging Considerationsmentioning
confidence: 99%
“…The synthetic aperture method requires a lot of calculations, and as a result, such equipment is expensive [4,5]. There is a demand for methods that can be integrated directly into existing commercial ultrasound devices [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Although PWI and SAI have shown potential in raising the frame rate limit, their real-time realization is inherently not a trivial implementation task. One technical challenge that concerns many system developers is the massive computational demand of these fast imaging methods as compared to conventional ultrasound image formation [4]. Existing ultrasound scanners are usually equipped with field programmable gate arrays (FPGA) and digital signal processors (DSP) to handle computations related to image formation [1].…”
Section: Introductionmentioning
confidence: 99%